The Comparison of Neuroticism/Psychoticism, Introversion/Extroversion and Coping Styles in Students of Families with Religious and Non-Religious Attitude - Somaieh Namazi; Shiva Karimkhani; Mariam Setaiesh; Fateme Seidi Rad (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objective: The family as a social institution has an important role in children's psychological development. This study was examined the neuroticism-psychoticism, introversion-extroversion and coping styles in Students whose families believe in religion in comparison with secular families. Method: The present study was a causal-comparative study. The statistical population was all the middle school students in Kermanshah City, in 2016. 380 people were selected using Krejcie and Morgan table and multi-stage cluster sampling. They completed ROQ (by their parents), EPQ-AF and CISS questionnaires. Data were analyzed using descriptive statistics, ANOVA and Tukey tests. All ethical issues were observed. Moreover, the authors did not report conflict of interest. Results: Correlation and analysis of variance showed that personality dimensions of neuroticism and psychoticism have negative correlation with problem-oriented coping style and avoidance coping style, positive relation  (P<0.001). Extraversion- showed positive relationship with problem oriented coping style and negative relationship with the emotion and avoidance, (P<0.001). Also, results showed that neuroticism, psychosis and extroversion were higher in non-religious people and religious people more than other people used Problem-focused coping style (P<0.001). Conclusion: According to this study, religious belief has inhibitory role in the occurrence of mental disorders. Thus strengthening the foundations of religious beliefs in society, especially in students is an effective step in prevention. For downloading the full-text of this article please click here.